New State Based Algorithm For Rubik’s Cube - Jery, Jeslin (International Journal of Computer Sciences and Engineering, 2019)
Rubik's cube is a 3-dimensional mechanical puzzle. The aim of this research paper is to describe a new algorithm which is state based to solve the Rubik's cube. There 40 quintillion possibilities to solve this problem. Hence without knowing the principles behind cube it is nearly impossible to solve in proper manner. It will take you through everything in order to solve the Rubik's cube. It is really simple, you just need to follow the algorithm and you will be solving Rubik's cube in less than two minutes. This paper on how to do the Rubik’s Cube will take about 45 minutes to understand, but once you get, you can impress all your friends with how you can solve one of life’s great mysteries: how to do a Rubik’s Cube.